Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran IPS Tema 8 Subtema 2 Menggunakan Model RADEC (Penelitian Tindakan Kelas Pada Pembelajaran IPS VI Tema 8 Subtema 2 Sekolah Dasar Negeri Cikalang 2 Kecamatan Tawang Kota Tasikmalaya) - Nurfauzi, Muhammad Ihsan; Mahendra, Hatma Heris; Zahra, Riza Fatimah (Jurnal Pendidikan Rafflesia, 2024)
This research aims to improve student learning outcomes in social studies subjects Theme 8 Subtheme 2 Using the RADEC Model. The problem in this research is the low value of students' learning outcomes in social studies subjects on the geographical location of ASEAN countries which is seen from the test results obtained which is still considered low because the average social studies learning outcomes of class VI students is still low. This is shown by the Social Sciences learning results of class VI students at SDN CIKALANG 2 during the daily repeat test, out of 30 students, 12 students completed with a percentage of 40% and 18 did not complete with a percentage of 60%. The method in this research uses the analytical design method, used to focus on the model refined by Arikunto in (Iskandar et al. 2015 p. 23) explaining that one PTK cycle consists of 4 steps, namely: 1 planning, 2 implementation, 3 observations, and 4 reflexes. The research results show that the RADEC learning model is effective in improving social studies learning outcomes regarding currencies and characteristics of ASEAN countries. Learning planning in cycles I and II was very good (80.55% and 90.27%), with an increase of 9.25%. The implementation of learning shows an increase in teacher activity (80% to 90.27%) and students (82.5% to 92.5%) between cycles I and II, with learning outcomes increasing from 59.83% (pre-cycle) to 75, 16% (cycle II).